2018
DOI: 10.1016/j.joto.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

An update on hearing impairment in patients with rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is a systemic, autoimmune disease that present with intra-articular and extra-articular manifestations. Auditory system may be involved during the course of RA disease due to numbers of pathologies. The link between hearing impairment and RA has been discussed in the previous literature. In this study we provide an update on the clinical aspect of hearing impairment in RA. We suggest to test hearing in all newly diagnosed RA patients at diagnosis as well as regularly during the course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…These findings have significant clinical implications because this frequency range is the most important for speech processing 23 . Hearing loss within this frequency range has also been reported in other systemic autoimmune diseases, including RA, AS, and SLE 24,25,26,27,28 .…”
Section: Discussionmentioning
confidence: 64%
“…These findings have significant clinical implications because this frequency range is the most important for speech processing 23 . Hearing loss within this frequency range has also been reported in other systemic autoimmune diseases, including RA, AS, and SLE 24,25,26,27,28 .…”
Section: Discussionmentioning
confidence: 64%
“…However, RA is known to have extra-articular manifestations (EAMs) involving the lungs, heart, eyes, skin, ears, and other body structures. Sensorineural hearing loss (SNHL) is the most prevalent form of hearing impairment in rheumatoid arthritis, with a prevalence rate between 12% and 80% [ 4 ]. Studies have reported that SNHL affects high frequency, although middle and low frequencies have also been seen [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other etiologies have been linked to drugs such as salicylates, non-steroidal anti-inflammatory drugs, and disease-modifying antirheumatic drugs. More so, environmental factors, such as smoking, alcohol, and exposure to noise, have been shown to affect the auditory system in healthy individuals and patients with RA [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…While hearing impairment has been reported to occur in up to 60% of patients with RA, its pathogenesis is not clear [ 11 ]. Sensorineural hearing loss was the most common hearing impairment, occurring in up to 80% of cases, following by conductive hearing loss [ 13 , 15 ]. While conductive hearing loss can be caused by arthritis of the incudostapedial and incudomalleolar joints, sensorineural hearing loss can be associated with inflammation of the inner ear, as well as vasculitis, neuritis, or deposition of immune complex, which result in cochlear damage [ 15 - 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sensorineural hearing loss was the most common hearing impairment, occurring in up to 80% of cases, following by conductive hearing loss [ 13 , 15 ]. While conductive hearing loss can be caused by arthritis of the incudostapedial and incudomalleolar joints, sensorineural hearing loss can be associated with inflammation of the inner ear, as well as vasculitis, neuritis, or deposition of immune complex, which result in cochlear damage [ 15 - 18 ]. The risk factors for hearing impairment in RA include old age, male, long disease duration, and anti-citrullinated peptide antibody (ACPA) positivity [ 13 - 15 ].…”
Section: Introductionmentioning
confidence: 99%